Economics of Aus Rice (Oryza sativa) and Jute (Corchorus olitorius) Cultivation in Some Selected Areas of Narsingdi District of Bangladesh (The Agriculturists, 2012)
The present study was conducted to estimate the relative profitability of growing aus rice and jute and to determine the resource use efficiency in the production of these crops in three selected village of Raipura upazila in Narsingdi. A total of 60 farmers were interviewed to collect primary data of which 30 farmers were produced aus rice and another 30 farmers were produced jute. Total costs for producing jute and aus rice were Tk 50254 and 44970 per hectare, respectively. The equivalent gross returns were Tk 83717 and Tk 55762, respectively. Accordingly, net return for jute was Tk 33463, which was about 3 times higher than that for aus rice (Tk. 10792/hectare). Moreover, BCR of producing jute was about 30% higher (1.7) than that of aus rice (1.3). Cobb-Douglas production function was used to estimate specific effects of individual inputs on production of jute and aus rice. Resource use efficiency analysis showed that neither jute nor aus rice farmers was efficient enough to use various inputs. Therefore, it seems that efficient and judicious use of various resources would enable both jute and aus rice farmers to earn more profit. DOI: http://dx.doi.org/10.3329/agric.v10i2.13145 The Agriculturists 2012; 10(2) 90-97